Pengaruh Produk, Harga, Distribusi Jasa Asuransi Syariah dalam Meningkatkan Loyalitas Nasabah Pada Kantor Agency Pru Cahaya Madani PT. Prudential Makassar - Miftahur Rahman Hafid; Yusram Adi; Ansar Taufik (Jurnal Online Manajemen ELPEI, 2023)
This study aims to explain the influence of the marketing mix (X) which consists of three variables, namely product, price, distribution on sales (Y). The population of this study was customers of the Agency office pru cahaya madani PT. Prudential Makassar, with a sample determination method using the slovin method and the number of samples studied was 98 respondents (people). The results of the analysis of this study use SPSS which can show the results of the F test and t test. From the F test ( simultaneous test) states that the free variables (X) studied simultaneously have a meaningful influence on increasing the loyalty of sharia insurance customers at the office of the civil service agency PT Prudential Makassar (Y). It is known that the value of Fhitung is 13.403 which means that it is greater than Fhitung than Ftabel (32,198 > 0.05). This means that statistically the product variables, prices, distribution, prudential sharia insurance products simultaneously have a meaningful influence on increasing the loyalty of sharia insurance customers of pt Prudential Makassar. As for the t test (partial test), it is known that the three variables are product, price, distribution, significant product to the loyalty of sharia insurance customers at the agency office pru cahaya madani PT. Prudential Makassar.